Implementasi dan Pengembangan Media Pembelajaran Game Flash Card untuk Meningkatkan Literasi dan Numerasi di SD Negeri Sumberejo - Argik Fitroh Magfiroh; Rika Agustin Puspitasari; Wadhatu Somadiya; Annita Mahmudah; Arian Yusuf Wicaksono; Didik Puji Wahyono; Sri Yaumi (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The Flashcard Game is a game that uses a number of cards measuring 25x30 cm which are written on letters of the alphabet and numbers with attractive designs and colors so that they can attract students' interest in playing the Flashcard Game. Specifically, the aim of this community service activity is to investigate the level of effectiveness of the literacy and numeracy program implemented at the selected school, namely Sumberejo State Elementary School. This service uses a learning method using flashcard game media. Implementing Flashcard Games to increase students' learning motivation in reading and arithmetic.